Rislevfundets Dyreknogler - Møhl, U. (Kuml, 1961)
The Animal Bones of the Rislev Find. The following summary description of the animal bones from the votive depository at Rislev is written as a supplement to Johs. and Klaus Ferdinand's archaeological account above. The bones have been transferred to the Copenhagen Zoological Museum and will not here be subjected to a detailed description with measurements, tables and figures 1) but merely to a brief survey with a discussion of the most significant points. From the zoological point of view, the Rislev find is extremely valuable. It includes a very large number of complete skulls and limb bones belonging to the same animals and so presents us with a section of the local livestock during the Roman Iron Age (4th century, A.D.). The excavation has brought a depository to light consisting either of whole animals or, particularly in the case of the horses, of parts of animals, viz. the head and the lower parts of the legs. Such a circumstance enhances the zoological value of the find far above the mere number of different breeds or the total number of the animals. The votive find was made up of the following different animals: horse (Equus caballus), at least 11 specimens, pig (Sus scrofa domesticus), at least 3 specimens, ox (Bos taurus domesticus), at least 7 specimens, sheep (Ovis aries), at least 5 specimens, dog (Canis familiaris), at least 3 specimens. Furthermore, there were the bones of some "outsiders" such as water rat (Arvicola terrestris), goose (Anser sp.), water rail (Rallus aquaticus) and pike (Esox lucius), which can hardly be presumed to have been involved in the votive rites. At least 29 domestic animals have thus been offered at these sacrifices where, it must be supposed that horses and dogs have occupied a special position among domestic animals; this fact is indicated by the bones in this and in other finds, in later Viking grave finds also, corresponding to our own attitude to these animals at the present day 4). Horse (Equus caballus). A significant and characteristic feature of the find is that of the 11 horses, particularly of the parts deposited, viz. the head (pole-axed and, in one case, with the severed tail stuck between the jaws) and the lowest parts of the 4 legs (severed at the carpal and tarsal bones respectively as is proved by several cutting marks on these bones). This constellation of the bones was found for nos. I-VI of the 11 horses; of the remaining 5 (nos. VII-XI), more or less "complete" sets of foot bones were found, but the skulls were lacking. Neither the sex nor the age of the sacrificial animals seems to have been a decisive factor; there are the bones of quite young horses (foals), of horses in their prime, and of old and decrepit animals. Although, in the following, an approximate age has been attempted, this must remain problematic, particularly with regard to the older animals, as nutrition, about which practically nothing is known with certainty, affects the abrasion of the teeth upon which the assessment of age is based. No. I is a mare (♀) c. 18 years, with much abraded teeth; no. II a quite young mare (a colt), c. l½ years; no. III a stallion (♂), c. 6 years; no. IV a stallion, just fully grown, c. 3 years; no. V a mare, c. 10 years; no. VI a very old mare, c. 25 years with teeth deeply abraded. The "obligatory" number of bones was found of these 6 horses, but the remaining 5 were, as already stated, represented only by the bones of the lowest part of the legs. These bones also, however, evidence animals of various ages. Taken all in all, the selection of livestock is large, but whether this is a mere chance or whether it is significant for this form of offering can only be determined by the discovery of further deposits of the same kind. The bone measurements evince a considerable variation in the size of the Rislev horses but they fall within the range of measurements covered by horses of the well-known Icelandic types. Among the Rislev horses there are also primitively proportioned animals the ratio of whose limb bones correspond both to the wild horse and to the Icelandic pony; this is true, for example, of the metacarpal and metatarsal bones of horse XI. The metacarpal index of these bones (i. e. the midbreadth expressed as a percentage of the length) is 16, the corresponding figure for the wild horse (Vedelshave, Fyn, Allerød period) is 16.3 and for the modem Icelandic pony (CN 1011), it is 16.1. The equivalent index for the metatarsal bone is 12 for all 3 breeds alike and so the congruence is considerable. Otherwise this index varies in the Rislev stock from 13.6 to 16 for the metacarpal bones and from 10.7 to 12 for the metatarsal. The exact total length of 10 metacarpal bones from Rislev varies from 188 to 216 mm, average length, 203 mm. The corresponding figures for 11 metatarsal bones are: total length from 226 to 255 mm, average length, 243 mm. The corresponding bones from the Viking and Middle Ages are, on the whole, longer and more slender. In size and shape, the Rislev horses may thus be said to bear a strong resemblance to the modem Icelandic pony, although the limb bones suggest that they were of a slighter build, while the skulls were also smaller and more finely formed, bringing the resemblance closer to horses of later periods, viz. the Viking and Middle Ages; but, as has been stated already, breeds of a more primitive and more robust type also occurred. This great variation stands, as has often been seen before, especially in the case of domestic animals, in relation to the size of the material. The Rislev find of 11 horses gives, therefore, an unusually good example of the variation in the livestock of the time. Other skeletal parts of these 11 horses are confined to a few, isolated bones, all bearing distinct signs of having been crushed or marrow-split; although of great cultural interest, these fragments are without zoological significance; they consist of only 11 pieces (the so-called "horse XII", vid. p. 60). The Domestic Ox (Bos taurus domesticus). The 7 oxen in the votive depository included calves and adult animals of both sexes. The connection between the skulls and the other bones is not so clear in the case of the oxen as in the horses. All the bones with one exception (ox I) are exceedingly crushed and split. Of ox I, a well preserved skull and mandible, neck vertebrae, ribs and several limb bones were found. The skull is intact. Its harmonious form, its curved cores of the horns and its narrow forehead all point to its having been that of a cow. Its ontogenetic age, judged by the abrasion of the teeth, may be put to something over 4½ years. The skull is more slender and more finely formed than that of a Jersey cow (which has a short, snub skull with great width of forehead between the eye sockets), but yet it is not so long as the skulls of modem breeds, for instance, "Black and White Danish". Its proportions can be indicated by expressing the greatest width of forehead (the distance at the back of the interorbital depression at the upper edge) as a percentage of the total length. In the Rislev cow this figure is 44.3, in the Jersey cow, it is 48 and in the modem Black and White Danish, it is 41.1. As regards the length/breadth ratio, the Rislev cow appears, thus, to have been a cross between these 2 modern extremes, with a closer resemblance to the longifrons breed. The limb bones, too, point to its having been a small cow. As the whole of one foreleg was found, the shoulder height may be calculated. This is 106 cm, the Jersey cow is c. 120 cm, the Red Dane cow, c. 130 cm, whereas a small, mediaeval cow (st. Valby, near Slagelse, c. 1400) only measured 102 cm. The skull and mandibles of ox II were found. This is a powerful, massively shaped skull, undoubtedly belonging to a bull. Although the skull is intact from the external occipital condyles to, and including, the intermaxillary bones, the whole of the upper frontal surface with the cores is missing. The frontal part that has been preserved (the interorbital part) shows clear marks of crushing blows. In comparison with the cranial dimensions, this ox has relatively small teeth. The length of the upper row (p2-m3) is 123 mm, a Jersey cow measures 119 mm and a Black and White Danish bull is 144 mm. The other cranial measurements, particularly the cephalic index, are considerably greater than those of both the Jersey cow and the Black and White, but this must be chiefly attributed to dimorphism of sex; there is nothing to indicate its not having belonged to the same breed as the cow (ox I). Tooth abrasion indicates an age of 5-6 years. Of the remaining 5 oxen, only a limited number of bones or fragments of bones have been found. Ox II is a calf of under 6 months, of which a number of distinctly marrow-split bones were found; this is remarkable as the marrow in such young bones was not usually extracted. Ox IV is an adult cow (c. 4 years). Its bones are all crushed and broken and include parts of the skull, the lower jaw and the lower parts of the 4 legs (vid. further below). Ox V consists of the broken fragments of both the skull and limb bones, but, apart from the teeth, which indicate the age as 6 years, they do not furnish sufficient material for a proper judgment. Ox VI also, is only represented by fragments of limb bones and vertebrae, but, from the unfused epiphyses, appears to have been about 2 years old. All that can be attributed to ox VII are about 6 fragments and the right mandible with milk teeth indicating an age of under 6 months and comparable with ox III. Apart from the skulls of oxen I and Il, the fragments of the above mentioned ox IV must be considered the most significant of the find, and, since we have succeeded in assembling these fragments to form the almost complete bones of both the right and left metacarpals and metatarsals (vid. fig. 70), definite measurements have been obtained, from which the interesting fact emerges that one of the smallest oxen known from prehistoric times was living in this country during the Roman Iron Age. Hitherto, the Middle Ages have been considered and described as that period in which oxen of minimum size were found, as has also been corroborated by the material found. But we have here an adult ox (c. 4 years) with such small limb bones (metacarpal and metatarsal) that its equal can hardly be found until over a thousand years later when we have a few bones from Rugtved (c. 1400) and from Vesterbygden, Greenland (c. 1000-1360, where special circumstances have obtained). The value is further enhanced by the significant fact that corresponding minimal ox bones have since been found in no fewer than 2 closely parallel votive finds (partially deposited sacrificial animals) from the Iron Age. These finds, Bukkerup and Turup, Fyn, were excavated by Albrectsen 2-3) in 1943 and 1957 respectively. They are dated to the 1st century A.D. and are, thus, somewhat earlier than the Rislev find. The majority of the ox bones from these finds are of the same minimum size; in one case the measurements are identical with those of the above mentioned Rislev cow. The ox bones from the Bukkerup find are nearly all extremely small in size as was mentioned by Degerbøl in Alhrectsen's account of the find. The following measurements from these 3 Iron Age votive finds show the uniform size of these pygmy oxen. The maximum length of the metacarpus is for Rislev (ox IV) 159 mm. The Bukkerup oxen vary between 160 and 175 mm (after Degerbøl) (7 bones), and the Turup oxen between 159 and 180 mm (4 bones). The cephalic index and the dimensions of the remaining limb bones are likewise of minimum size. Although a single measurement only equals that of the Rislev cow, most of the bones fall within the range of this small breed. These bones are remarkably small, yet they are exceptionally harmoniously formed and do not appear to be small as a result of degeneration or of malnutrition. They seem to be the representatives of a very small but healthy and harmonious breed that has come into this country in this form in the Roman Iron Age (possibly in connection with the votive rites of the time as is evinced by the Rislev, Bukkerup and Turup finds). It must be remembered that the earlier the archaeological period in which the bones of these pygmy oxen are found and the smaller their bones, the more certain is the conclusion that this breed was introduced to this country in this form and that it is not the result of a greater or lesser diminution of the size of the local stock. Sheep (Ovis aries). Sheep comprise no insignificant part of the Rislev find. So far as it has been possible to ascertain, there seems to have been at least 5 animals, 2 older sheep, 1 younger and 2 lambs. Sheep I is of special zoological significance since, similarly to several other domestic animals, the skull and all 4 legs were found. The limb bones are unharmed (not marrow-split) but the skull shows with drastic clarity that the animal had been pole-axed. Furthermore, the cores of the horns have been severed at the base (probably in the flaying). The rows of molars are intact and show advanced abrasion. The length of the upper row (p2-m3) is 65.5 mm. A sheep from Store Karlsø has exactly the same measurements while a modem Icelandic sheep measures 67 mm. This Rislev sheep has belonged to the breed with goatlike horns (Ovis aries palustris) and the limb bones show that it has been a very small sheep, one of the smallest known in this country. The maximum length of the metacarpal and metatarsal bones are 120 and 127 mm respectively, figures which correspond with those of indigenous Faroe sheep (Lille Dimon, 1845) measuring 121 and 132 mm, while the corresponding bones of large, modem breeds are as much as 162 and 176 mm. The remaining sheep bones are mostly of younger animals, not fully grown. These bones consist of 2 half mandibles and some limb bones belonging to 2 lambs of 2 and 4 months respectively. In addition, situated in the original peat bank (vid. p. 50 fig. 3), were both the mandibles and most of the bones of the fore and hind legs of a lamb of about 1 year, sheep II, with milk teeth showing incipient abraison of m2. From the same field, the fragment of the right mandible of an old sheep of c. 5 years was recovered. Thus, on the whole, the sheep bones also demonstrate a depository of the head and legs. Pig (Sus scrofa domesticus). Bones of this animal occurred only sparsely and can hardly represent more than 2 or 3 specimens. There are the skull and the fragments of the lower jaw of a pig of 11-12 months. These fragments (10.9 a and B. 17) may, according to their ontogenetic age, very well have belonged to the same animal, although they were found in different fields. A symphysis fragment (1.6) is from an older animal of c. 3 years. Apart from these fragments, there were only a few, isolated, juvenile limb bones and some ribs. The material is, therefore, too scant for exact measurements, but the general impression, evinced by the 2 symphysis fragments, which are weak and slight, is that the Rislev pigs have also been small animals. Dog (Canis Familiaris). The skeletal fragments were found of at least 3 dogs which varied in size and age but which were all dogs of average size, well-proportioned both as to skull and limb and whose shoulder height was 45-55 cm, i. e. somewhat smaller than modem sporting dogs such as pointers and the like. Of dog I was found the well preserved skull (A 3) and, presumably, also a thigh bone (A 4) with severe pathological malformation of the lower part. The skull is powerfully formed with a capacious, somewhat short cranium, a broad, flat forehead with a slight interorbital depression and an even slant towards the nose. The molars are powerful, regularly posed, without interdental spaces or crowding. There is greatly advanced abrasion, especially of the canines and molars. The skeleton of dog II was found in several, albeit, adjacent fields and it cannot be assumed with certainty that all the bones derive from the same animal. Certain ontogenetical differences (the different degrees of fusion of the epiphyses) make it possible for there to have been more than 1 animal, although a certain variation of this factor may occur. The skull (C 14) and the mandibles (C I and C 40) all belong to the same animal: a younger dog, a little over 1 year old and only slightly larger than dog I but with a less capacious cranium and rather weaker teeth, quite unabraded. The coronal sutures are unclosed and the external occipital crest (crista sagittalis) is more powerfully developed than in the older skull (dog I). Dog II has presumably been a male; the limb bones are all rather long and slenderly built. Of dog III were found the most important parts of the whole skeleton 1); the skull is, practically speaking, of the same length as that of dog I, but it is narrower and of finer build, the cervical index is smaller throughout and the frontal slant is less pronounced. The cranium itself is of the same arched, capacious type and the teeth are only slightly smaller than those of the others and so are in fine accordance with the proportions of the skull. The tooth abrasion in this case is complete abrasion of the enamel of all cusps. The age of this dog lies between the 2 afore mentioned and the fusion of the epiphyses is seen completed for all bones. This fully grown dog may well be presumed to be a bitch of fine build. The variation between these dogs is no greater than may exist between different individuals of the same breed. They are well proportioned, of average size and considerably smaller than the well known "great" dogs of the Iron Age such as the Hjortspring (Pre-Roman Iron Age) and the dog from Tibirke Bog (c. 200 A.D.) or the dog from Dalshøj, Bornholm (Pre-Roman Iron Age) and the dog from Lille Lyngby (500-1000 A.D.). On the other hand, the Rislev dogs are considerably larger than the small palustris breeds as, for instance, the Bundsø dogs of the Neolithic Age. The length of the skull (the condylobasal length) of the Rislev dog lies between 167 and 188 mm. The Bundsø dog measures from 136 to 161 mm 6) and the above mentioned "great" dogs measure between 195 and 206 mm 4). The Rislev dogs thus form a very considerable addition to the material from the Roman Iron Age and seem to have their own peculiar features. From the zoological point of view, the greatest importance of the Rislev find lies in the many horses, the little ox and the 3 dogs all taken in relation to the period and to the exceptionally fine state of preservation of the skulls and limb bones. U. Møhl.